Current‐Induced Nucleation and Annihilation of Magnetic Skyrmions at Room Temperature in a Chiral Magnet. Issue 21 (29th March 2017) - Yu, Xiuzhen; Morikawa, Daisuke; Tokunaga, Yusuke; Kubota, Masashi; Kurumaji, Takashi; Oike, Hiroshi; Nakamura, Masao; Kagawa, Fumitaka; Taguchi, Yasujiro; Arima, Taka‐hisa; Kawasaki, Masashi; Tokura, Yoshinori
Abstract : A magnetic skyrmion is a nanometer‐scale magnetic vortex carrying an integer topological charge. Skyrmions show a promise for potential application in low‐power‐consumption and high‐density memory devices. To promote their use in applications, it is attempted to control the existence of skyrmions using low electric currents at room temperature (RT). This study presents real‐space observations for the current‐induced formation and annihilation of a skyrmion lattice (SkL) as well as isolated skyrmions in a microdevice composed of a thin chiral magnet Co8 Zn9 Mn3 with a Curie temperature, T C ≈ 325 K, above RT. It is found that the critical current for the manipulation of Bloch‐type skyrmions is on the order of 10 8 A m −2, approximately three orders of magnitude lower than that needed for the creation and drive of ferromagnetic (FM) domain walls in thin FM films. The in situ real‐space imaging also demonstrates the dynamical topological transition from a helical or conical structure to a SkL induced by the flow of DC current, thus paving the way for the electrical control of magnetic skyrmions. Abstract : Electric‐current‐induced formation of a skyrmion lattice (SkL) and domainboundary (DB) motion (between the SkL and a helical (H) or conical structure) are demonstrated in a microdevice, composed of a thin magnet Co‐Zn‐Mn with non‐centrosymmetric structure. The threshold current for manipulation of skyrmions is on the order of 10 8 A m −2 .